PENGUKURAN PROSES DAN HASIL PROSES BENTANG ALAM JAWA TENGAH - Dwi Lestari (DEPARTMENT OF GEOGRAPHY EDUCATION, UNIVERSITY OF JEMBER, 2019)
References SARI, Eva Kurnia; PRAMESTY, Dinda Ayu. THE EFFECT OF VEHICLES INTENSITY IN SUMBERSARI JEMBER REGENCY. Geosfera Indonesia, [S.l.], v. 3, n. 3, p. 50-58, jan. 2019. ISSN 2614-8528. Available at: <https://jurnal.unej.ac.id/index.php/GEOSI/article/view/9300>. Date accessed: 26 july 2019. doi: https://doi.org/10.19184/geosi.v3i3.9300. KURNIANTO, Fahmi Arif et al. THE ENVIRONMENT ANALYSIS OF POPULATION GROWTH, UNEMPLOYMENT, AND POVERTY LEVEL IN MAESAN DISTRICT BONDOWOSO REGENCY. Geosfera Indonesia, [S.l.], v. 3, n. 2, p. 113-121, aug. 2018. ISSN 2614-8528. Available at: <https://jurnal.unej.ac.id/index.php/GEOSI/article/view/8439>. Date accessed: 26 july 2019. doi: https://doi.org/10.19184/geosi.v3i2.8439. IKHSAN, Fahrudi Ahwan et al. GEOGRAPHY LITERACY OF OBSERVATION INTRODUCTION LANDSCAPE REPRESENTATION PLACE FOR STUDENT EXPERIENCE. Geosfera Indonesia, [S.l.], v. 3, n. 2, p. 131-145, aug. 2018. ISSN 2614-8528. Available at: <https://jurnal.unej.ac.id/index.php/GEOSI/article/view/8384>. Date accessed: 26 july 2019. doi: https://doi.org/10.19184/geosi.v3i2.8384. KURNIANTO, Fahmi Arif et al. GEOGRAPHIC INFORMATION SYSTEM (GIS) APPLICATION TO ANALYZE LANDSLIDE PRONE DISASTER ZONE IN JEMBER REGENCY EAST JAVA.Geosfera Indonesia, [S.l.], v. 2, n. 1, p. 45-53, apr. 2018. ISSN 2614-8528. Available at: <https://jurnal.unej.ac.id/index.php/GEOSI/article/view/7524>. Date accessed: 26 july 2019. doi: https://doi.org/10.19184/geosi.v2i1.7524. IKHSAN, Fahrudi Ahwan et al. GEOGRAPHY SKILLS DOMAIN TAXONOMY. Geosfera Indonesia, [S.l.], v. 2, n. 1, p. 54-59, apr. 2018. ISSN 2614-8528. Available at: <https://jurnal.unej.ac.id/index.php/GEOSI/article/view/7525>. Date accessed: 26 july 2019. doi: https://doi.org/10.19184/geosi.v2i1.7525. NURDIN, Elan Artono et al. DEMOGRAPHIC FACTORS INFLUENCE ON POPULATION ADDED IN SUMBERSARI JEMBER DISTRICT.Geosfera Indonesia, [S.l.], v. 2, n. 1, p. 60-66, apr. 2018. ISSN 2614-8528. Available at: <https://jurnal.unej.ac.id/index.php/GEOSI/article/view/7515>. Date accessed: 26 july 2019. doi: https://doi.org/10.19184/geosi.v2i1.7515. APRIYANTO, Bejo et al. THE INFLUENCE OF TEAM ASSISTED INDIVIDUALIZATION (TAI) ON GEOGRAPHY LEARNING MODEL TEAM OF JUNIOR HIGH SCHOOL. Geosfera Indonesia, [S.l.], v. 2, n. 1, p. 83-88, apr. 2018. ISSN 2614-8528. Available at: <https://jurnal.unej.ac.id/index.php/GEOSI/article/view/7529>. Date accessed: 26 july 2019. doi: https://doi.org/10.19184/geosi.v2i1.7529. KURNIANTO, Fahmi Arif et al. LEVEL OF KNOWLEDGE OF SENIOR HIGH SCHOOL STUDENTS TO MANGROVE CONSERVATION.Geosfera Indonesia, [S.l.], v. 1, n. 1, p. 8-15, dec. 2017. ISSN 2614-8528. Available at: <https://jurnal.unej.ac.id/index.php/GEOSI/article/view/6190>. Date accessed: 26 july 2019. doi: https://doi.org/10.19184/geosi.v1i1.6190. KURNIANTO, Fahmi Arif et al. LEVEL OF KNOWLEDGE OF SENIOR HIGH SCHOOL STUDENTS TO NORTH COASTAL OF JAVA CONSERVATION. Geosfera Indonesia, [S.l.], v. 1, n. 1, p. 22-28, dec. 2017. ISSN 2614-8528. Available at: <https://jurnal.unej.ac.id/index.php/GEOSI/article/view/6192>. Date accessed: 26 july 2019. doi: https://doi.org/10.19184/geosi.v1i1.6192.